Structural and compressibility properties of weft-knitted rib fabrics from glass yarn - Mehmet Erdem İnce (MANAS: Journal of Engineering)
The structural and compressibility properties of the weft-knitted glass yarn fabrics from 1x1, 2x2, English, and fisherman rib architectures were investigated in this study. Due to their tight structures; 2x2 and fisherman rib fabric architectures exhibited higher loop density, and shorter loop length than 1x1 and English rib fabric architectures. English and fisherman rib fabric architectures displayed higher fiber volume fraction than 1x1 and 2x2 rib architectures in multi-layer compaction and recovery tests where the pressure was varied between 2 and 200 kPa. Number of layer increased the fiber content that pointed the nesting between the fabric layers. As a result of lack of complete recovery from compression; the fabrics exhibited lower thicknesses (i.e. higher fiber volume fractions) during the recovery periods than they did during the compression periods. A second order polynomial regression model with 0,89 R2 (coefficient of determination) was developed to estimate the fiber volume fraction by means of knit architecture, number of fabric layers, pressure, and measurement period.